Promosi Produk Jajanan Korea Melalui Instagram di Masa Pandemi Covid-19 - Fasya Maulida Firdhani; Anne Ratnasari (UNISBA Press, 2023)
Absract. Eonnie Kitchen is a culinary business that focuses on Korean snacks. From the beginning of its appearance, Eonnie Kitchen has marketed its products online, from WhatsApp to Instagram. During the current Covid-19 pandemic, there have been many changes in the activities of citizens around the world. Starting from shopping, working, until studying is also carried out online. Eonnie Kitchen uses Instagram to introduce and promote products to followers and potential followers. The purpose of this research is the promotion of Korean snack products during the Covid-19 pandemic which was carried out by Eonnie Kitchen through Instagram social media. This study uses a qualitative method with a case study approach. Data were collected by interview, observation and documentation techniques. The results of this study are 1). Promotion of Eonnie Kitchen products on Instagram using advertising, sales promotion and public relations. 2). Utilization of Instagram @eonnie.kitchen Features in promoting products using several Instagram features including: uploading photos or videos, photo titles or captions, comments, Instagram stories, Instagram reels, and Instagram live. 3). Eonnie Kitchen's mainstay of viral content is Korean drama content, trending content, and content with viral sound (music) and movement (dancing). With viral content, Eonnie Kitchen can reach more people. Abstrak. Eonnie Kitchen adalah sebuah usaha kuliner yang berfokus pada jajanan korea. Dari awal kemunculannya eonnie kitchen sudah memasarkan produk secara online, mulai dari WhatsApp sampai Instagram. Di masa pandemi Covid-19 saat ini, telah banyak memberi perubahan aktivitas warga di seluruh penjuru dunia. Dimulai belanja, bekerja, sampai belajar juga dilaksanakan dalam online. Eonnie Kitchen menggunakan Instagram untuk memperkenalkan dan mempromosikan produk kepada followers dan calon followers. Tujuan dari penelitian ini yaitu promosi produk jajanan Korea di masa pandemi Covid-19 yang dilakukan oleh Eonnie Kitchen melalui media sosial instagram. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan dengan teknik wawancara, observasi, dan dokumentasi. Hasil penelitian ini adalah 1). Bentuk promosi produk Eonnie Kitchen di Instagram dengan menggunakan advertising, sales promotion, dan public relations. 2). Pemanfaatan Fitur Instagram @eonnie.kitchen dalam mempromosikan produk dengan menggunakan beberapa fitur Instagram meliputi : unggah foto atau video, judul foto atau caption, komentar, instagram story, instagram reels, dan instagram live. 3). Konten-konten viral yang menjadi andalan Eonnie Kitchen yaitu konten drama korea, konten tren, dan konten dengan sound (musik) dan gerakan (jogetan) viral. Dengan konten-konten viral, Eonnie Kitchen dapat lebih menjangkau banyak orang.